A genetically engineered H5 protein expressed in insect cells confers protection against different clades of H5N1 highly pathogenic avian influenza viruses in chickens. Issue 2 (4th March 2017) - Oliveira Cavalcanti, Marcia; Vaughn, Eric; Capua, Ilaria; Cattoli, Giovanni; Terregino, Calogero; Harder, Timm; Grund, Christian; Vega, Carlos; Robles, Francisco; Franco, Julio; Darji, Ayub; Arafa, Abdel-Satar; et al.
ABSTRACT: The evolution of highly pathogenic H5N1 avian influenza viruses (HPAI-H5N1) has resulted in the appearance of a number of diverse groups of HPAI-H5N1 based on the presence of genetically similar clusters of their haemagglutinin sequences (clades). An H5 antigen encoded by a recombinant baculovirus and expressed in insect cells was used for oil-emulsion-based vaccine prototypes. In several experiments, vaccination was performed at 10 days of age, followed by challenge infection on day 21 post vaccination (PV) with HPAI-H5N1 clades 2.2, 2.2.1, and 2.3.2. A further challenge infection with HPAI-H5N1 clade 2.2.1 was performed at day 42 PV. High haemagglutination inhibition titres were observed for the recH5 vaccine antigen, and lower haemagglutination inhibition titres for the challenge virus antigens. Nevertheless, the rate of protection from mortality and clinical signs was 100% when challenged at 21 days PV and 42 days PV, indicating protection over the entire broiler chicken rearing period without a second vaccination. The unvaccinated control chickens mostly died between two and five days after challenge infection. A low level of viral RNA was detected by reverse transcription followed by a quantitative polymerase chain reaction in a limited number of birds for a short period after challenge infection, indicating a limited spread of HPAI-H5N1 at flock level. Furthermore, it was observed that the vaccine can be used in a differentiation infected from vaccinated animals (DIVA) approach, based on the detection of nucleoprotein antibodies in vaccinated/challenged chickens. The vaccine fulfilled all expectations of an inactivated vaccine after one vaccination against challenge with different clades of H5N1-HPAI and is suitable for a DIVA approach.